Climate Smart Village project in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
This series of interventions highlighted in this video are part of CGIAR-CCAFS initiatives being implemented under the banner of Climate Smart Villages in Vaishali, Bihar